Beautiful beadwork from nature : 16 stunning jewelry projects inspired by the natural world - Shippee, Melissa (Lark Books, 2019)
6 gorgeous beaded jewelry projects for intermediate-to-advanced beaders, featuring one-of-a-kind, nature-inspired designs. Drawing from the shapes, colors, and beauty of the natural world, award-winning jewelry designer Melissa Shippee has fashioned a breathtaking collection of wearable art. From delicate earrings made of graceful beaded flowers to a showstopping crystal fringe necklace inspired by ancient stalactites, each striking project uses popular materials such as seed beads, crystals, and Czech glass beads. Along with illustrated step-by-step instructions, a basics section provides a refresher on essential beadweaving techniques. A gallery of works from top artists offers additional inspiration.